Effect of Nursing Empowerment Program on Adaptation in Breastfeeding for Mother with Preterm Infants - Sivichai, Atiporn (Journal of Health Science of Thailand, 2017)
The purpose of this study was assess the effectiveness of an empowerment model to promote breastfeeding among mothers with preterm infant. Participants were mothers who gave birth to preterm infants and were treated in newborn intensive care, Phra Nakhon Si Ayutthaya Hospital. Target group of this research was selected through purposive sampling to recruit 40 mothers. The study samples were divided into a control group (n = 20) receiving the usual nursing care and an experimental group (n = 20) participating in the Nursing Empowerment Program. Data were collected by using questionnaires which were (1) maternal adaptation questionnaires and (2) evaluation form of maternal empowerment of which Cronbach’s alpha coefficients were 0.81 and 0.76, respectively; and the data were analyzed by using independent t-test. It was found that the level of maternal adaptation on breastfeeding for mother with preterm infants who received the Nursing Empowerment Program was significantly higher than those who received the usual nursing care (p<0.01). The finding suggested that the Nursing Empowerment Program could be implemented in order to enhance maternal adaptation in breastfeeding for mother with preterm infants. The program should be applied to the routinely nursing practice to promote the success of breastfeeding in preterm infants.